Penerapan Pendekatan Pembelajaran Kooperatif Tipe Student Teams Achievement Division untuk Meningkatkan Hasil Belajar Luas Bangun Datar Murid Kelas V SD Inpres 5/81 Awo I Kabupaten Bone - Padja langi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The main problem of this research is whether through the STAD type cooperative learning approach the results of the fifth grade students of SD Inpres 5/81 Awo I, Bone Regency, can improve the learning outcomes of flat shapes. While the purpose of this study is to improve learning outcomes of flat shapes through cooperative learning with the Student Teams Achievement Divisions type approach for fifth grade students of SD Inpres 5/81 Awo I, Bone Regency. Data collection using observation techniques to filter data on student activities and teacher actions during the process. In learning, learning outcomes tests are used to collect student achievement data, the analysis used is descriptive statistical analysis in the form of percentages and frequency tables. The results showed: student learning achievement increased on the subject of broad-level learning using the Cooperative Learning Approach Type of Student Teams Achievement Division. The conclusion of this study is that the students' learning outcomes of flat shapes using the Student Teams Divisions type for fifth grade students of SD Inpres 5/81 Awo I, Bone Regency, improved mathematics learning outcomes, increased learning outcomes of flat shapes learning outcomes were carried out through the Student Teams Divisions (STAD) type. ) based on the level of interest, experience, and skills of students in relation to the subject being taught.